2009
DOI: 10.1902/jop.2009.090236
|View full text |Cite
|
Sign up to set email alerts
|

Serum Inflammatory Mediators in Pregnancy: Changes After Periodontal Treatment and Association With Pregnancy Outcomes

Abstract: Objective To determine: 1) if periodontal treatment in pregnant women before 21 weeks of gestation alters levels of inflammatory mediators in serum; and 2) if changes in these mediators are associated with birth outcomes. Methods 823 pregnant women with periodontitis were randomly assigned to receive scaling and root planing before 21 weeks of gestation or after delivery. Serum obtained between 13 weeks and 16 weeks 6 days (study baseline) and 29–32 weeks gestation was analyzed for C-reactive protein, prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 36 publications
4
34
0
Order By: Relevance
“…This led to the hypothesis of a potential link between periodontal diseases and obstetrical complications like preterm birth, as Offenbacher and his colleagues [14] first demonstrated in 1996. Other authors suggested that such link may be related to systemic changes induced by inflammation and immune response [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This led to the hypothesis of a potential link between periodontal diseases and obstetrical complications like preterm birth, as Offenbacher and his colleagues [14] first demonstrated in 1996. Other authors suggested that such link may be related to systemic changes induced by inflammation and immune response [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Again, studies of varying size and quality have been carried out in a range of geographical locations, and these have not all reported the same pattern of results. While it has been established that periodontal treatment in pregnancy can improve oral health 111,112 and be matched by beneficial changes in oral microbiological status, 113 the majority of large well executed studies have failed to show any effect of nonsurgical periodontal treatment on the incidence of adverse pregnancy outcomes, [112][113][114][115][116][117] and this has been supported by systematic reviews. 118,119 It is unclear why treatment has failed to show improvements even though other data suggest that it may be expected to do so.…”
Section: Does This Mean That Treatment Helps Reduce Risk?mentioning
confidence: 99%
“…However, "biomarkers" such as biochemical components of gingival crevicular fluid and venous blood [e.g., prostaglandins (PGE 2 ), interleukins IL1β, IL6, IL8, IL12, TNFα, Creactive protein, fibrinogen, interferonγ] are commonly included as outcome measures in clinical trials (i.e., Machtei and Younis, 2008;Michalowicz et al, 2009;Renvert et al, 2009;Vidal et al, 2009). Those who design, conduct, and evaluate the results of such trials must carefully consider the significance of biomarker findings, because they may or may not be consistent with clinically mean ingful endpoints.…”
Section: Clinical and Surrogate Endpoints (Outcomes) And Biomarkersmentioning
confidence: 99%